Glucokinase activity in the arcuate nucleus regulates glucose intake. - Hussain,S; Richardson,E; Ma,Y; Holton,C; De,Backer I; Buckley,N; Dhillo,W; Bewick,G; Zhang,S; Carling,D; Bloom,S; Gardiner,J (J Clin Invest, 2015)
The brain relies on a constant supply of glucose, its primary fuel, for optimal function. A taste-independent mechanism within the CNS that promotes glucose delivery to the brain has been postulated to maintain glucose homeostasis; however, evidence for such a mechanism is lacking. Here, we determined that glucokinase activity within the hypothalamic arcuate nucleus is involved in regulation of dietary glucose intake. In fasted rats, glucokinase activity was specifically increased in the arcuate nucleus but not other regions of the hypothalamus. Moreover, pharmacologic and genetic activation of glucokinase in the arcuate nucleus of rodent models increased glucose ingestion, while decreased arcuate nucleus glucokinase activity reduced glucose intake. Pharmacologic targeting of potential downstream glucokinase effectors revealed that ATP-sensitive potassium channel and P/Q calcium channel activity are required for glucokinase-mediated glucose intake. Additionally, altered glucokinase activity affected release of the orexigenic neurotransmitter neuropeptide Y in response to glucose. Together, our results suggest that glucokinase activity in the arcuate nucleus specifically regulates glucose intake and that appetite for glucose is an important driver of overall food intake. Arcuate nucleus glucokinase activation may represent a CNS mechanism that underlies the oft-described phenomena of the "sweet tooth" and carbohydrate craving.